Saving Natural Forests - Kushalapa, K. A. (Indian Forester, 1992)
The ecological balance is being upset due to the rapid rise of human population and their increased demands for more utilisation of natural resources. The existing natural forests are protecting our living environment. Therefore, to save the ecosystem, it is necessary to pay a special attention to protect, preserve and maintain the natural forests.